Patterns of vascularization and surgical morbidity in juvenile nasopharyngeal angiofibroma: A case series, systematic review, and meta‐analysis. Issue 2 (11th November 2017) - Overdevest, Jonathan B.; Amans, Matthew R.; Zaki, Peter; Pletcher, Steven D.; El‐Sayed, Ivan H.
Abstract: Background: Vascular patterns of juvenile nasopharyngeal angiofibroma (JNA) are poorly defined. We performed both institutional and systematic literature reviews to characterize the relationship between arterial supply patterns of JNA with intraoperative blood loss and tumor recurrence. Methods: A retrospective review of 26 patients with JNA treated at our institution from 1995 to 2015 with available angiograms, and systematic reviews and meta‐analyses of 828 JNA cases undergoing angiographic embolization published between 1995 and 2015 were completed per Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Results: The systematic review (828 cases) found internal carotid artery (ICA) supply in 35.6% of tumors, and 30.8% of tumors received bilateral vascular supply. Our institutional data (n = 26) indicated 69% had bilateral supply. Meta‐analysis of data from 5 studies demonstrated ICA/bilateral arterial supply is predictive of increased operative blood loss ( P < .01). Conclusion: Complex vascular contributions to JNA are frequent, underreported, and portends increased blood loss. This information can justifiably be included in staging systems to enhance prognostic counseling of patients.